Prevalence and Correlates of Emotional, Physical, Sexual, and Financial Abuse and Potential Neglect in the United States: The National Elder Mistreatment Study - Acierno, Ron (American Public Health Association, 2010)
Objectives. We estimated prevalence and assessed correlates of emotional, physical, sexual, and financial mistreatment and potential neglect (defined as an identified need for assistance that no one was actively addressing) of adults aged 60 years or older in a randomly selected national sample. Methods. We compiled a representative sample by random digit dialing across geographic strata. We used computer-assisted telephone interviewing to standardize collection of demographic, risk factor, and mistreatment data. We subjected prevalence estimates and mistreatment correlates to logistic regression. Results. We analyzed data from 5777 respondents. One-year prevalence was 4.6% for emotional abuse, 1.6% for physical abuse, 0.6% for sexual abuse, 5.1% for potential neglect, and 5.2% for current financial abuse by a family member. One in 10 respondents reported emotional, physical, or sexual mistreatment or potential neglect in the past year. The most consistent correlates of mistreatment across abuse types were low social support and previous traumatic event exposure. Conclusions. Our data showed that abuse of the elderly is prevalent. Addressing low social support with preventive interventions could have significant public health implications.